2013
DOI: 10.1007/s12072-013-9486-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of a combined hepatitis B virus surface and core antigen vaccine in patients with chronic hepatitis B

Abstract: HBsAg/HBcAg vaccine seems a safe and efficient therapeutic approach for patients with CHB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 30 publications
6
56
0
Order By: Relevance
“…Recombinant HBcAg, in combination with HBsAg, has been evaluated in chronic hepatitis B patients, resulting in normalized ALT levels in all of them and no detectable HBV DNA in half of them [36,42] . These results support further evaluations of the combined HBV antigens we have reported in this study as therapeutic reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant HBcAg, in combination with HBsAg, has been evaluated in chronic hepatitis B patients, resulting in normalized ALT levels in all of them and no detectable HBV DNA in half of them [36,42] . These results support further evaluations of the combined HBV antigens we have reported in this study as therapeutic reagents.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that NASVAC was safe and efficiently overcome the immune tolerance in CHB patients. 61 In the following phase IIb/III clinical trial, 160 CHB patients were enrolled, 151 of them completed the trial. 75 patients received 100 mg HBsAg and 100 mg HBcAg 5 times.…”
Section: Hbsag Combines Antiviral Drugsmentioning
confidence: 99%
“…The phase I/II trial in Bangladesh enrolled 18 treatment-naïve patients [9]. The vaccine was administered ten times at 2-weekly intervals, the first five doses via nasal route only and the subsequent five doses via both nasal and subcutaneous routes.…”
Section: Clinical Phase Of Developmentmentioning
confidence: 99%
“…The vaccine is based on a combination of the HBsAg and the HBV nucleocapsid (HBcAg) antigens and is simultaneously administered by the intranasal and subcutaneous routes [6,7]. ABX203 has been studied in phase I, phase II and phase III clinical trials with promising results [8][9][10]. In the present work we reviewed the results of the main preclinical and clinical trials of this product.…”
mentioning
confidence: 99%